Method for improving crosslinking uniformity of hydroxyethyl cellulose
Through surfactant dispersion and protection technology, the problem of poor cross-linking uniformity of hydroxyethyl cellulose is solved, its solubility and light transmittance are improved, and a more stable cross-linking effect is achieved.
Patent Information
- Application Number
- CN202411498275.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-10
AI Technical Summary
The existing hydroxyethyl cellulose crosslinking process has problems such as poor crosslink uniformity, poor crosslinking effect or excessive crosslinking, resulting in poor dissolution performance and solution light transmittance.
The hydroxyethyl cellulose is dispersed and protected by surfactants. Through specific surfactants mixing and cross-linking reaction sequence and conditions, the uniformity of glyoxal cross-linking is improved, and the hemiacetals are prevented from continuing to react, forming a stable Crosslinked structure.
It significantly improves the solubility of hydroxyethyl cellulose and the light transmittance of aqueous solution, avoids excessive crosslinking, and obtains crosslinking products with better uniformity.
Smart Images

Figure CN119286005A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cellulose production, and specifically relates to a method for improving the cross-linking uniformity of hydroxyethyl cellulose. The method can effectively improve the uniformity of glyoxal cross-linking of hydroxyethyl cellulose products, and improve the dissolution time, dissolution performance and light transmittance of aqueous solution of the products. Background Art
[0002] Hydroxyethyl cellulose (HEC) is an important water-soluble cellulose ether. Its main properties are that it is soluble in both cold water and hot water, has a wide viscosity range, good thermal stability, and has the properties of thickening, emulsification, dispersion, bonding, adhesion, suspension, film-forming, antimicrobial, water retention, and salt resistance. It is widely used in coatings, daily chemicals, petroleum extraction, construction, polymer synthesis, pesticides and other industries.
[0003] There are many hydrophilic groups on the hydroxyethyl cellulose molecule. The hydroxyethyl cellulose that has not been cross-linked will start to dissolve immediately when it meets water. However, the hydroxyethyl cellulose product is in the form of solid powder or granules. During use, the material is not completely evenly dispersed when it is just added to the water. There are agglomerates or granular materials. The hydroxyethyl cellulose on the outside dissolves when it meets water, and the powder inside is wrapped inside. Due to the excellent thickening and water retention properties of hydroxyethyl, it takes a long time for the powder wrapped inside to completely dissolve. Therefore, it is usually necessary to cross-link the hydroxyethyl cellulose (i.e., instant dissolution treatment) so that the hydroxyethyl cellulose will not dissolve immediately and become sticky when it meets water, but can be suspended and dispersed in water under stirring. Since the hemiacetal formed by the cross-linking reaction is not stable enough, the cross-linking bonds begin to break over time, and the hydroxyethyl cellulose begins to gradually dissolve in the water, so that a uniformly dissolved hydroxyethyl cellulose aqueous solution can be obtained in a relatively short time.
[0004] When cross-linking hydroxyethyl cellulose, glyoxal or other substances providing aldehyde functional groups are usually used as cross-linking agents. Hemiacetal is formed in the process of cross-linking with hydroxyethyl cellulose, which reduces its water-soluble performance, thereby improving the problem of hydroxyethyl cellulose becoming sticky and forming core-coating when it dissolves in water. However, hemiacetal is generally unstable and can continue to undergo acetalization reaction with hydroxyl groups (i.e., excessive cross-linking) to form an epoxy ether structure, thereby reducing the number of hydrophilic hydroxyl groups in the polymer, resulting in poor water solubility and light transmittance of hydroxyethyl cellulose products and reduced viscosity. When acetalization reaches a certain degree, the product may even be completely insoluble in water.
[0005] In CN107325333B, trehalose and hydroxyethyl cellulose are cross-linked, mainly because trehalose has a reducing disaccharide structure, which can provide aldehyde functional groups under certain conditions, react with HEC to form a cross-linked structure, thereby obtaining a fast-dissolving cross-linked hydroxyethyl cellulose product. In "Study on the Preparation and Cross-linking Treatment of Hydroxyethyl Cellulose (HEC) Fiber" (Donghua University; Zhang Peng; Master's Electronic Journal Publishing Information, Issue 05, 2014), glyoxal is used for cross-linking, and the reaction is carried out for 30 minutes under the conditions of pH 4 and cross-linking temperature of 40°C to obtain a cross-linked hydroxyethyl cellulose product.
[0006] Both of the above methods use aldehyde functional groups to react with the active hydroxyl functional groups of hydroxyethyl cellulose to form hemiacetal, thereby obtaining a cross-linked hydroxyethyl cellulose product. However, both methods have problems such as poor cross-linking uniformity, poor cross-linking effect or excessive cross-linking due to the continued reaction of hemiacetal, which leads to poor solubility of hydroxyethyl cellulose and poor light transmittance of the solution. Summary of the invention
[0007] In order to solve the problems that the existing cross-linking process is prone to poor cross-linking uniformity, poor cross-linking effect or excessive cross-linking, which leads to poor solubility of hydroxyethyl cellulose and poor light transmittance of the solution, the present invention first mixes and disperses hydroxyethyl cellulose with a surfactant evenly, and then cross-links the material with glyoxal and another surfactant and uniformly disperses, mixes and encapsulates the material, so as to obtain a hydroxyethyl cellulose product with uniform cross-linking.
[0008] To achieve the above object, the present invention provides a method for improving the cross-linking uniformity of hydroxyethyl cellulose, which comprises the following steps:
[0009] A. dispersing surfactant m in water to obtain surfactant m slurry;
[0010] B. dispersing surfactant n in diluent solvent q to obtain surfactant n slurry;
[0011] C. Evenly mixing the hydroxyethyl cellulose and the surfactant m slurry to obtain a mixed material;
[0012] D. adding a crosslinking agent, glyoxal, and a surfactant n slurry to the mixed material of step C to carry out a crosslinking reaction;
[0013] E. After the cross-linking reaction is completed, the hydroxyethyl cellulose is dried, crushed and sieved to obtain uniformly cross-linked hydroxyethyl cellulose;
[0014] In step A, the surfactant m is a polycarboxylate anionic surfactant, a polyacrylate anionic surfactant or a sulfonate anionic surfactant;
[0015] In step B, the surfactant n is a polyoxyethylene nonionic surfactant or a fatty acid glyceride surfactant;
[0016] In step C, the mass ratio of surfactant m to hydroxyethyl cellulose in the surfactant m slurry is 0.2-3.0:100;
[0017] In step D, the mass ratio of surfactant n in the surfactant n slurry to the hydroxyethyl cellulose in step C is 0.1-2.0:100.
[0018] Preferably, in the above method for improving the cross-linking uniformity of hydroxyethyl cellulose, in step A, the surfactant m is sodium polycarboxylate, potassium polycarboxylate, sodium polyacrylate or sodium succinate sulfonate.
[0019] Wherein, in the above method for improving the cross-linking uniformity of hydroxyethyl cellulose, in step A, the mass ratio of the surfactant m to water is 1.0-2.0:1.0.
[0020] Preferably, in the above method for improving the cross-linking uniformity of hydroxyethyl cellulose, in step B, the surfactant n is polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan fatty acid ester, polyoxyethylene sorbitan monooleate or glyceryl monostearate.
[0021] Wherein, in the above method for improving the cross-linking uniformity of hydroxyethyl cellulose, in step B, the dilution solvent q is at least one of isopropanol, tert-butyl alcohol or acetone.
[0022] Wherein, in the above method for improving the cross-linking uniformity of hydroxyethyl cellulose, in step B, the mass ratio of the surfactant n to the dilution solvent q is 1:9-10.
[0023] Preferably, in the above method for improving the cross-linking uniformity of hydroxyethyl cellulose, in step C, the mass ratio of the surfactant m to the hydroxyethyl cellulose in the surfactant m slurry is 0.5-2.0:100.
[0024] Wherein, in the above method for improving the cross-linking uniformity of hydroxyethyl cellulose, in step C, the pH value of the hydroxyethyl cellulose is 6.0-8.0.
[0025] Wherein, in the above method for improving the cross-linking uniformity of hydroxyethyl cellulose, in step C, the uniform mixing is performed by stirring and mixing for 30 to 90 minutes.
[0026] Preferably, in the above method for improving the cross-linking uniformity of hydroxyethyl cellulose, in step D, the mass ratio of surfactant n in the surfactant n slurry to the hydroxyethyl cellulose in step C is 0.5-1.0:100.
[0027] Wherein, in the above method for improving the cross-linking uniformity of hydroxyethyl cellulose, in step D, the mass ratio of glyoxal to the hydroxyethyl cellulose in step C is 0.5-1.0:100.
[0028] Wherein, in the above method for improving the cross-linking uniformity of hydroxyethyl cellulose, in step D, the cross-linking reaction is a stirring reaction for 20 to 60 minutes.
[0029] Wherein, in the above method for improving the cross-linking uniformity of hydroxyethyl cellulose, in step D, the temperature of the cross-linking reaction is room temperature (generally 10 to 30° C.).
[0030] Wherein, in the above method for improving the cross-linking uniformity of hydroxyethyl cellulose, in step E, the drying temperature is 80-100°C.
[0031] In the present invention, the glyoxal used is a commercially available 40% glyoxal solution; when calculating the amount of glyoxal used, the pure glyoxal in the glyoxal solution is used for measurement.
[0032] Beneficial effects of the present invention:
[0033] The present invention disperses and protects hydroxyethyl cellulose molecules by using a surfactant, utilizes the dispersing effect of the surfactant m to evenly disperse the material to improve the uniformity of glyoxal cross-linking, and then utilizes the surfactant n to wrap and protect the cross-linked hydroxyethyl cellulose. The addition sequence and amount of the two are controlled at the same time, so as to improve the uniformity of glyoxal cross-linking and prevent hemiacetal from continuing to react with active hydroxyl groups of other hydroxyethyl celluloses to form an acetal, thereby improving the solubility of the HEC product and the light transmittance of the aqueous solution. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The present invention is a process flow chart for preparing cross-linked hydroxyethyl cellulose.
[0035] Figure 2 Schematic diagram of the structure of uncross-linked hydroxyethyl cellulose.
[0036] Figure 3 Schematic diagram of the structure of glyoxal-crosslinked hydroxyethyl cellulose.
[0037] Figure 4 The schematic diagram is a structural diagram of cross-linked hydroxyethyl cellulose prepared by the surfactant of the present invention. DETAILED DESCRIPTION
[0038] Specifically, a method for improving the cross-linking uniformity of hydroxyethyl cellulose comprises the following steps:
[0039] A. dispersing surfactant m in water to obtain surfactant m slurry;
[0040] B. dispersing surfactant n in diluent solvent q to obtain surfactant n slurry;
[0041] C. Evenly mixing the hydroxyethyl cellulose and the surfactant m slurry to obtain a mixed material;
[0042] D. adding a crosslinking agent, glyoxal, and a surfactant n slurry to the mixed material of step C to carry out a crosslinking reaction;
[0043] E. After the cross-linking reaction is completed, the hydroxyethyl cellulose is dried, crushed and sieved to obtain uniformly cross-linked hydroxyethyl cellulose;
[0044] In step A, the surfactant m is a polycarboxylate anionic surfactant, a polyacrylate anionic surfactant or a sulfonate anionic surfactant;
[0045] In step B, the surfactant n is a polyoxyethylene nonionic surfactant or a fatty acid glyceride surfactant;
[0046] In step C, the mass ratio of surfactant m to hydroxyethyl cellulose in the surfactant m slurry is 0.2-3.0:100;
[0047] In step D, the mass ratio of surfactant n in the surfactant n slurry to the hydroxyethyl cellulose in step C is 0.1-2.0:100.
[0048] In the early stage, the inventors compared and preliminarily selected the performance of anionic surfactants, cationic surfactants, zwitterionic surfactants and nonionic surfactants based on common surfactants, and then respectively used stearic acid, sodium dodecylbenzene sulfonate, sodium polycarboxylate, potassium polycarboxylate, sodium polyacrylate, sodium succinate sulfonate, lecithin, fatty acid glyceride, fatty acid sorbitan, polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan fatty acid ester, polyoxyethylene sorbitan monooleate and other surfactants to carry out screening tests, and compared the addition ratios thereof. According to the test, surfactant m needs to select polycarboxylate anionic surfactant, polyacrylate anionic surfactant or sulfonate anionic surfactant, and surfactant n needs to select polyoxyethylene nonionic surfactant or fatty acid glyceride surfactant. At the same time, the inventors combined the characteristics of hydroxyethyl cellulose products such as strong water absorption of materials and the presence of agglomerated granular materials, and targetedly first used surfactants with excellent dispersibility to evenly disperse the materials to avoid agglomeration, avoid the problem that the materials inside the particles cannot be contacted with the crosslinking agent for reaction, and then carry out crosslinking reaction and material encapsulation, so as to achieve the best effect. Therefore, the present invention must first add surfactant m and then surfactant n; if added in reverse order, the material is wrapped first, which cannot solve the problem of agglomerated particles in the material, and will directly affect the cross-linking reaction, thereby affecting the solubility of the product and the transmittance of the aqueous solution.
[0049] In step A of the present invention, the surfactant m selected is a polycarboxylate anionic surfactant, a polyacrylate anionic surfactant or a sulfonate anionic surfactant; preferably, the surfactant m is sodium polycarboxylate, potassium polycarboxylate, sodium polyacrylate, sodium succinate sulfonate, and such surfactants have the characteristics of low pH and temperature sensitivity, high dispersion stability, and are not easy to settle and flocculate, and can disperse the hydroxyethyl cellulose material well and improve the fluidity of the material; the surfactant is diluted with water, and the mass ratio of the surfactant m to the dilution solvent water is 1.0-2.0:1.0. Since such dispersants themselves have a certain viscosity, dilution can reduce their fluidity for easy transportation on the one hand, and can also be better mixed with the hydroxyethyl cellulose material on the other hand, thereby improving the dispersion effect of the material.
[0050] In step B of the present invention, the selected surfactant n is a polyoxyethylene nonionic surfactant or a fatty acid glyceride surfactant; preferably, the surfactant n is polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan fatty acid ester, polyoxyethylene sorbitan monooleate or glyceryl monostearate. Such surfactants have excellent dispersing, emulsifying, stabilizing and other properties, and are very compatible with other types of surfactants, and can better wrap and disperse the materials; the mass ratio of surfactant n to diluent solvent q is 1:9-10, and such dispersants are mostly pastes or waxes, and their fluidity can be improved by dilution, and they can be better mixed with the materials; the diluent solvent q is at least one of isopropanol, tert-butyl alcohol or acetone, which are commonly used solvents in the production of hydroxyethyl cellulose.
[0051] In step C of the present invention, the mass ratio of surfactant m to hydroxyethyl cellulose is 0.2-3.0:100, preferably 0.5-2.0:100, and the stirring mixing time is 30-90 minutes. The pH of hydroxyethyl cellulose is neutral (pH is 6.0-8.0). Since hydroxyethyl cellulose has strong hydrophilicity, the material easily absorbs moisture and agglomerates. The surfactant m is fully mixed with hydroxyethyl cellulose at room temperature to make the hydroxyethyl cellulose material in a uniformly dispersed state.
[0052] In step D of the present invention, the mass ratio of surfactant n to hydroxyethyl cellulose is 0.1-2.0:100, preferably 0.5-1.0:100, the mass ratio of glyoxal to hydroxyethyl cellulose is 0.5-1.0:100, the stirring and mixing reaction is carried out for 20-60 minutes, and the crosslinking reaction temperature is room temperature (generally 10-30° C.). In step C, the hydroxyethyl cellulose material in a uniformly dispersed state undergoes a crosslinking reaction with glyoxal, and the aldehyde functional group reacts with the active hydroxyl functional group of the hydroxyethyl cellulose to form hemiacetal. At the same time, the crosslinked hydroxyethyl cellulose is wrapped by the dispersing, emulsifying and stabilizing properties of surfactant n, preventing the hemiacetal from continuing to undergo an acetalization reaction with the active hydroxyl groups of other hydroxyethyl cellulose molecules to cause excessive crosslinking and affect the solubility of the product.
[0053] In step E, the material is dried at 80-100° C., and then crushed and sieved to obtain a uniformly cross-linked hydroxyethyl cellulose product. Rapid drying under high temperature conditions removes the solvent and moisture in the material system, avoids the destruction of the cross-linking and encapsulation morphology of the product, and thus obtains a stable cross-linked hydroxyethyl cellulose product.
[0054] In step C of the present invention, the hydroxyethyl cellulose used is uncrosslinked hydroxyethyl cellulose, which can be prepared by conventional methods in the art; the general preparation steps are: using powdered cellulose as a raw material and a mixed solvent (a mixture of isopropyl alcohol, tert-butyl alcohol and water) as a medium, reacting cellulose with sodium hydroxide to generate alkali cellulose; then reacting the alkali cellulose with ethylene oxide to generate crude hydroxyethyl cellulose, neutralizing the alkali in the reaction system with an acid, and then washing and drying to obtain uncrosslinked hydroxyethyl cellulose.
[0055] The present invention is further described in detail below by way of examples, but the protection scope of the present invention is not limited to the scope of the examples.
[0056] The raw materials in the embodiment are: hydroxyethyl cellulose (industrial grade), isopropyl alcohol (99.9%), tert-butyl alcohol (99.9%), acetone (99.9%), tap water, sodium polycarboxylate (reagent), sodium polyacrylate (reagent), sodium succinate sulfonate (reagent), polyoxyethylene sorbitan monolaurate (reagent), polyoxyethylene sorbitan fatty acid ester (reagent), polyoxyethylene sorbitan monooleate (reagent), and glyoxal (40%).
[0057] Example 1
[0058] 100 g of sodium polycarboxylate anionic surfactant was fully mixed and diluted with 100 g of water to obtain 200 g of sodium polycarboxylate anionic surfactant solution. 20 g of polyoxyethylene sorbitan monolaurate was fully mixed and dissolved with 180 g of isopropyl alcohol to obtain 200 g of polyoxyethylene sorbitan monolaurate solution.
[0059] Add 1000g of hydroxyethyl cellulose product to the middle of a high-speed mixer, then add 40g of sodium polycarboxylate anionic surfactant solution, mix and disperse for 30min at room temperature; then add 25g of 40% glyoxal and 80g of polyoxyethylene sorbitan monolaurate solution, and cross-link for 30min; after the reaction, dry the material at 85°C, and then crush and screen to obtain a uniformly cross-linked hydroxyethyl cellulose product.
[0060] Example 2
[0061] 100 g of sodium polyacrylate anionic surfactant was fully mixed and diluted with 100 g of water to obtain 200 g of sodium polyacrylate anionic surfactant solution. 20 g of polyoxyethylene sorbitan fatty acid ester was fully mixed and dissolved with 180 g of acetone to obtain 200 g of polyoxyethylene sorbitan fatty acid solution.
[0062] Add 1000g of hydroxyethyl cellulose product to the middle of a high-speed mixer, then add 24g of sodium polyacrylate anionic surfactant solution, mix and disperse for 30min at room temperature; then add 20g of 40% glyoxal and 100g of polyoxyethylene sorbitan fatty acid solution, and carry out cross-linking reaction for 30min; after the reaction, dry the material at 95°C, and then crush and screen to obtain a uniformly cross-linked hydroxyethyl cellulose product.
[0063] Example 3
[0064] 100 g of sodium polycarboxylate anionic surfactant was fully mixed and diluted with 50 g of water to obtain 150 g of sodium polycarboxylate anionic surfactant solution. 20 g of polyoxyethylene sorbitan monooleate was fully mixed and dissolved with 200 g of tert-butyl alcohol to obtain 220 g of polyoxyethylene sorbitan monooleate solution.
[0065] Add 1000g of hydroxyethyl cellulose product to the middle of a high-speed mixer, then add 10.5g of sodium polycarboxylate anionic surfactant solution, mix and disperse for 30min at room temperature; then add 15g of 40% glyoxal and 55g of polyoxyethylene sorbitan monooleate solution, and cross-link for 30min; after the reaction, dry the material at 85°C, and then crush and screen to obtain a uniformly cross-linked hydroxyethyl cellulose product.
[0066] Analysis and testing
[0067] The present invention uses conventional cross-linked hydroxyethyl cellulose as a comparative example, and analyzes and tests Examples 1-3 and HEC respectively. The results are shown in Table 1.
[0068] Table 1 Analysis results
[0069]
[0070] Comparative Examples 1 and 2 are conventional cross-linked hydroxyethyl cellulose. Conventional cross-linking process of cross-linked hydroxyethyl cellulose: under stirring, glyoxal is directly sprayed onto uncross-linked hydroxyethyl cellulose to carry out a cross-linking reaction, thereby obtaining a cross-linked hydroxyethyl cellulose product.
[0071] As can be seen from Table 1, the present invention disperses and protects hydroxyethyl cellulose molecules by using surfactants, which significantly improves the solubility of the cross-linked HEC product and the light transmittance of the aqueous solution, and also improves the viscosity to a certain extent.
Claims
1. A method for improving the cross-linking uniformity of hydroxyethyl cellulose, characterized in that: The following steps are involved: A. dispersing surfactant m in water to obtain surfactant m slurry; B. dispersing surfactant n in diluent solvent q to obtain surfactant n slurry; C. Evenly mixing the hydroxyethyl cellulose and the surfactant m slurry to obtain a mixed material; D. adding a crosslinking agent, glyoxal, and a surfactant n slurry to the mixed material of step C to carry out a crosslinking reaction; E. After the cross-linking reaction is completed, the hydroxyethyl cellulose is dried, crushed and sieved to obtain uniformly cross-linked hydroxyethyl cellulose; In step A, the surfactant m is a polycarboxylate anionic surfactant, a polyacrylate anionic surfactant or a sulfonate anionic surfactant; In step B, the surfactant n is a polyoxyethylene nonionic surfactant or a fatty acid glyceride surfactant; In step C, the mass ratio of surfactant m to hydroxyethyl cellulose in the surfactant m slurry is 0.2-3.0:100; In step D, the mass ratio of surfactant n in the surfactant n slurry to the hydroxyethyl cellulose in step C is 0.1-2.0:
100.
2. The method for improving the cross-linking uniformity of hydroxyethyl cellulose according to claim 1, characterized in that: In step A, the surfactant m is sodium polycarboxylate, potassium polycarboxylate, sodium polyacrylate or sodium succinate sulfonate.
3. The method for improving the cross-linking uniformity of hydroxyethyl cellulose according to claim 1, characterized in that: In step A, the mass ratio of the surfactant m to water is 1.0-2.0:1.
0.
4. The method for improving the cross-linking uniformity of hydroxyethyl cellulose according to claim 1, characterized in that: In step B, the surfactant n is polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan fatty acid ester, polyoxyethylene sorbitan monooleate or glyceryl monostearate.
5. The method for improving the cross-linking uniformity of hydroxyethyl cellulose according to claim 1, characterized in that: At least one of the following is met: In step B, the dilution solvent q is at least one of isopropanol, tert-butanol or acetone; In step B, the mass ratio of the surfactant n to the dilution solvent q is 1:9-10.
6. The method for improving the cross-linking uniformity of hydroxyethyl cellulose according to claim 1, characterized in that: In step C, the mass ratio of surfactant m to hydroxyethyl cellulose in the surfactant m slurry is 0.5-2.0:
100.
7. The method for improving the cross-linking uniformity of hydroxyethyl cellulose according to claim 1, characterized in that: At least one of the following is met: In step C, the pH value of the hydroxyethyl cellulose is 6.0 to 8.0; In step C, the uniform mixing is performed by stirring and mixing for 30 to 90 minutes.
8. The method for improving the cross-linking uniformity of hydroxyethyl cellulose according to claim 1, characterized in that: In step D, the mass ratio of surfactant n in the surfactant n slurry to the hydroxyethyl cellulose in step C is 0.5-1.0:
100.
9. The method for improving the cross-linking uniformity of hydroxyethyl cellulose according to claim 1, characterized in that: At least one of the following is met: In step D, the mass ratio of glyoxal to hydroxyethyl cellulose in step C is 0.5-1.0:100; In step D, the cross-linking reaction is stirred for 20 to 60 minutes; In step D, the temperature of the cross-linking reaction is room temperature.
10. The method for improving the cross-linking uniformity of hydroxyethyl cellulose according to any one of claims 1 to 9, characterized in that: In step E, the drying temperature is 80-100°C.
Citation Information
Patent Citations
Instant hydroxyethyl cellulose and preparation method thereof
CN107325333B